Dimensi Keadilan Ekologis dalam Hukum Islam:Studi tentang Tanggungjawab Manusia sebagai Khalifah - Hasnia Hasnia; Kurniati; Misbahuddin (AL-MUTSLA, 2026)
The increasingly complex ecological crisis indicates the limitations of legal and policy approaches that have not fully succeeded in fostering human responsibility toward the environment. Islamic law, through the concept of khalifah fil ardh, provides a normative foundation that positions humans as trustees responsible for maintaining ecological balance and sustainability. This study aims to construct a model of khalifah based on ecological responsibility, analyze the opportunities and challenges of its implementation, and identify its impacts within legal and social contexts. This research employs a normative juridical method with statutory, conceptual, and philosophical approaches, analyzed qualitatively through literature study. The findings reveal that the ecological-based khalifah model is built upon the principles of mizan (balance), amanah (trust), and the prohibition of fasad (destruction), which are formulated into three dimensions: awareness, regulation, and implementation. Opportunities for implementation arise from the integration of religious values with national legal frameworks and the growing environmental awareness, while challenges include the dominance of anthropocentric paradigms, weak law enforcement, and conflicts between economic interests and environmental preservation. The implementation of this model contributes to strengthening legal norms, shaping environmentally responsible social behavior, and promoting ecological sustainability. This study underscores that integrating Islamic legal values into environmental governance offers a relevant framework for developing sustainable ecological justice.